1997
DOI: 10.1093/bja/79.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incremental doses of sevoflurane on cerebral pressure autoregulation in humans

Abstract: We have examined cerebral pressure autoregulation while awake, and during 0.5 and 1.5 MAC of sevoflurane anaesthesia in 10 patients undergoing non-intracranial neurosurgical procedures. All patients received a standardized anaesthetic comprising premedication with temazepam 20 mg orally, a sleep dose of propofol, fentanyl 1 microgram kg-1 and vecuronium 0.1 mg kg-1. After tracheal intubation, the lungs were ventilated with a mixture of air and oxygen to mild hypocapnia. Routine monitors included ECG, continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 25 publications
2
58
1
Order By: Relevance
“…In humans sevoflurane concentrations 1.5 MAC did not affect static cerebrovascular autoregulation. [20][21][22] However, studies in rats have shown that higher concentrations of sevoflurane (2.0 MAC) impair static cerebrovascular autoregulation in a fashion similar to other volatile anesthetics. 23 The dynamic component of cerebrovascular autoregulatory response, which appears to be a more sensitive indicator of altered physiology than the static component, was intact with 1.5 MAC sevoflurane, 24 but delayed with 2.0 MAC sevoflurane during the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In humans sevoflurane concentrations 1.5 MAC did not affect static cerebrovascular autoregulation. [20][21][22] However, studies in rats have shown that higher concentrations of sevoflurane (2.0 MAC) impair static cerebrovascular autoregulation in a fashion similar to other volatile anesthetics. 23 The dynamic component of cerebrovascular autoregulatory response, which appears to be a more sensitive indicator of altered physiology than the static component, was intact with 1.5 MAC sevoflurane, 24 but delayed with 2.0 MAC sevoflurane during the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Like all other volatile agents, sevoflurane causes dose-dependent cerebral vasodilatation, 20 however this effect is not as pronounced as it is with isoflurane. 16 Sevoflurane has been shown to effectively preserve cerebral blood pressure autoregulation 21 and cerebrovascular CO 2 reactivity. 22 In addition, induction and maintenance of anesthesia for children with sevoflurane represents common pediatric practice.…”
Section: Objectifmentioning
confidence: 99%
“…However, in the presence of preserved autoregulation changes in MAP values do not result in relative changes in CBFv. It has been shown that autoregulation is preserved during propofol anaesthesia and during sevoflurane anaesthesia up to a concentration of 1.5 MAC [7,21,22,36]. Therefore, the reduction in MAP values during anaesthesia with either anaesthetic agent, cannot explain the observed reduction of CBFv values.…”
Section: Discussionmentioning
confidence: 98%